Effect of Job Competency, Job Experience and Work Environment on Job Achievement at PT. XYZ, Juanda Branch, Central Jakarta - Viniyati Maftuchach; Fiona Sukma Salfadilla (Journal of Research in Business, Economics, and Education, 2020)
The research aims to obtain empirical evidence regarding job competence, job experience, work environment and job achievement on PT. XYZ, Tbk. Juanda Branch Central Jakarta. Independent variables in this study are job competence, job experience and work environment. Whereas the dependent variables are job achievements. The population in this study was the entire employee of PT. XYZ, Tbk. Central Juanda-Jakarta Branch. Samples obtained by as many as 42 respondents, sampling techniques using nonprobability sampling that is saturated sampling. The analysis technique used in the study was Multiple Linear Regression analysis in data processing using Smart PLS 3.2.7. The results of the analysis in this study suggest that all hypotheses are acceptable. Job competence has a positive effect on job achievement, job experience has a positive effect on job achievement and work environment has a positive effect on job achievement. It means employee job achievement on PT. XYZ, Tbk. The Central Juanda-Jakarta branch is heavily influenced directly by job competence, job experience, and work environment.